2020
DOI: 10.1371/journal.pone.0231748
|View full text |Cite
|
Sign up to set email alerts
|

Detecting vision loss in intermediate age-related macular degeneration: A comparison of visual function tests

Abstract: The purpose of the study was to evaluate the diagnostic accuracy of visual function tests in intermediate age-related macular degeneration (iAMD). A total of 62 subjects (38 patients with iAMD and 24 controls) were included and underwent several functional assessments: Best-corrected visual acuity (BCVA), low luminance visual acuity (LLVA), visual acuity (VA) measured with the Moorfields Vanishing Optotypes Acuity Charts (MAC), contrast sensitivity with the Pelli-Robson test, reading speed using the Internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 50 publications
(73 reference statements)
2
39
0
3
Order By: Relevance
“…The measurement of standard visual acuity (VA) is the basis of any visual function examination despite it being insensitive to early disease, or unable to differentiate different disease stages in many retinal conditions 1–4 . It is well established that vision under low luminance conditions is reduced compared with standard VA 5–8 .…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of standard visual acuity (VA) is the basis of any visual function examination despite it being insensitive to early disease, or unable to differentiate different disease stages in many retinal conditions 1–4 . It is well established that vision under low luminance conditions is reduced compared with standard VA 5–8 .…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, LLVA has been shown to capture visual impairment in nAMD better than standard distance acuity ( 41 ), there is currently limited data correlating systematically LLVA and various morphologic characteristics. The Chroma and Spectri studies reported a weak negative correlation between LLVA and GA lesion size at baseline and week 48 in bilateral GA in dry AMD ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dimitrov et al assessed a battery of visual function tests and concluded that contrast thresholds assessed using flickering targets could be used as optimal tests to assess visual function in AMD [ 21 ]. In a recently published study by Pondorfer et al [ 23 ], several visual function tests were found to be sensitive in differentiating normal from intermediate AMD subjects. While their general conclusion that contrast sensitivity and mesopic testing conditions are sensitive to elicit visual dysfunction in non-advanced AMD, are in general agreement with the results of our study, there are several differences in study methods between our study and Pondorfer et al’s.…”
Section: Discussionmentioning
confidence: 99%
“…Our goal was to develop functional tests that are capable of identifying subtle differences between these two groups and reliably capture underlying neuronal dysfunction in AMD at its earliest stage. While several previous studies have looked into sensitive visual function tests for early and intermediate stages of AMD [18,[21][22][23], our study is unique in that we focused on identifying tests that are sensitive but also relatively easy and simple to implement in clinical trial settings by focusing on cone-based tests. The test duration for each of the visual function tests described in this study is less than 5 min per eye.…”
Section: Introductionmentioning
confidence: 99%